PENINGKATAN KEMAMPUAN MENULIS PUISI MELALUI MEDIA PEMBELAJARAN âBENDERA PELANGIâ PADA SISWA KELAS VIIID SEMESTER GENAP SMP NEGERI 1 SUGIHWARAS KABUPATEN BOJONEGORO TAHUN PELAJARAN 2013 / 2014 - Hidayati, Nur Alfin (MAGISTRA, 2014)
Basically, learning the language means learning to communicate with others. In GBPP / main teaching guideline, Indonesian Language and Literature (Depdikbud, 1993: 3) it is mentioned that learning Indonesian language aimed to express ideas, opinions, experiences, and messages and feelings in oral or written discourses. Again, it is emphasized in a few Standart Competency and Competency Policy on Curriculum Education Unit, which is used as a platform of learning implementation at this time. Standart Competency mentions that students are able to express thoughts and feelings can be applied to the learning literature, both prose, poetry, or drama. Specially in learning poetry, the facts shows that the majority of teachers (including the author) find it difficult to teach poetry. It cannot be denied that, poetry is a form of literature in which the linguistic symbols used to expres feeling author (Sari Sastra Indonesia, Sumiati Budiman: 1987: 8). This study was carried out in SMP Negeri 1 Sugihwaras Regency Bojonegoro Year Education 2013/2014, which is focused in VIII-D. In order to be efficient and effective, the study was conducted in accordance with the schedule of teacherâs learning in the classroom or totally, there were 8X research meetings in VIII-D (4 weeks). The research was started in the beginning of mid- March to mid-April 2013. There were 34 students and 1 Drop Out 1 student. Thus, 33 students were the research focus. The data collection used are documentation, observation and a survey. There were 3 cycles in the research. In cycle 1, there is no significant improvement towards the students score. There was only 45 % , then in the second cycle was increasing in this study is 60 % and in the third cycle there is a significant improvement achieved in 80 %. Keyword: Writing Skill, Bendera Pelangi Model.